MENGUKUR INDEKS PEMBANGUNAN LITERASI MASYARAKAT (IPLM) KABUPATEN PROBOLINGGO - Fadhilatus Shoimah (PANGRIPTA, 2023)
To grow and improve community literacy and equitable distribution of people's quality of life in terms of ease of accessing information and knowledge, it is necessary to have a measurement to determine the value of the Community Literacy Development Index (IPLM) in Probolinggo Regency The research is carried out in stages, from research design, implementation of field surveys, data, to analysis. The value of the Probolinggo Regency Community Literacy Development Index (IPLM) in 2021 obtained a result of 10.67. The Community Literacy Development Index (IPLM) value of Probolinggo Regency is slightly lower than the National Community Literacy Development Index (IPLM) and Community Literacy Development Index (IPLM) of East Java Province at 12,993 and 13.44, respectively.